A NEW VALIDATED STABILITY-INDICATING DIRECT HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR THE DETERMINATION OF ROSIGLITAZONE ENANTIOMERS IN THE PRESENCE OF ITS DEGRADATION PRODUCTS - GOWRAMMA, BYRAN; MEYYANATHAN, SUBRAMANIYAN NAIYANAR; BABU, BASAWAN; KRISHNAVENI, NAGAPPAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: In the present study, an isocratic chiral reverse-phase high-performance liquid chromatography method was developed and the resolution of the drug and complete separation from its degradation products were successfully achieved. Methods: An isocratic method developed with a Phenomenex Lux 5 μ Cellulose 1 (150 mm×4.6 mm i.d., 5 μ) using UV detector at wavelength of 220 nm, with a mobile phase consisting of methanol:0.1% diethylamine (60:40% v/v) and a flow rate of 1 ml/min. The drug was subjected to alkaline, acidic, neutral, oxidative, and photolytic to apply stress conditions. The stressed samples were analyzed by the proposed method. Results: The described method was linear over the range of 3–7 μg/ml for R-enantiomer and 9–21 μg/ml of S-enantiomer, respectively. The limit of detection and limit of quantification of R and S enantiomers were found to be 0.56 μg/ml and 0.18 μg/ml, respectively. Conclusion: The method provides good sensitivity and excellent precision and reproducibility. The developed method can be applied in the quality control of drug products.